PERBEDAAN FUNGSI PARU PADA PEKERJA BERDASARKAN UNIT KERJA DI INDUSTRI TEPUNG TAPIOKA KECAMATAN MARGOYOSO KABUPATEN PATI - Rizki Nurul Mutmainnah; Onny Setiani; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The negative impact of the tapioca industry is the emergence of organic dust pollution originating from the processing of raw materials and the end products of industrial products. The resulting flour dust has the potential to pollute the work environment so that workers who are controlling the production activities will be exposed to dust which can cause lung function disorders. The purpose of this study was to analyze differences in pulmonary function (% FVC and FEV1 prediction value for workers based on total dust content in the Tapioca Industry of Kecamatan Margoyoso Kabupaten Pati. This study was an observational analytic study with a cross sectional approach. The research sample of 40 respondents was taken quota sampling from a population of 58 workers. The results of measurement of total dust using Middle Volume of Air Sampler in Sorting Unit = 10,5 mg/m3, Transport Unit = 4,3 mg/m3, Drying Unit= 0,9 mg/m3 and Milling Unit = 11,4 mg/m3. The results of measurement of lung function were 10% of workers experiencing restriction, 10% had mild restriction, 12,5% had mild obstruction, 2,5% had moderate obstruction and 20% had mixed disorders. The statistical test results of ANOVA with (α = 0,05) there are differences in lung function (FVC prediction value) with p-value = 0,001 and based on the Kruskal Wallis Test shows a difference in FEV1 predictive value with p-value = 0,001 in workers based on work units in Tapioca Industry of Kecamatan Margoyoso Kabupaten Pati and dust levels affect the incidence of pulmonary function disorders. It is recommended that companies install exhaust vans in work areas and monitor the use of masks regularly.